Realistic Terrain Aware Mobility Model - Dineska, Maja; Filiposka, Sonja (My University, 2012)
Among other simulation parameters, topology and mobility model are key factors for precise evaluation of ad hoc networking protocol characteristics. Because the movement of the nodes directly impacts protocol performance, it is essential to use realistic movement model that will provide improved simulation results. The majority of proposed mobility models in the current research literature do not provide realistic movement scenarios in a terrain modeled environment. They are often limited to random walk mobility models without considering real-world terrain. The work presented in this paper introduces R3D, an independent tool for generating mobility scenarios that follow a newly proposed 3D mobility model that includes nodes movements through real, irregular 3D terrain